Predictors of neonatal near-misses in Worabe Comprehensive Specialized Hospital, Southern Ethiopia - Yasin, Shemsu; Abdisa, Lemesa; Roba, Hirbo Shore; Tura, Abera Kenay (Frontiers in Pediatrics, 2024)
Abstract Background: Neonatal deaths are still a major leading cause of social and economic crises. Identifying neonatal near-miss events and identifying its predictors is crucial to developing comprehensive and pertinent strategies to alleviate neonatal morbidity and death. However, neither neonatal near-miss nor predictors of neonatal near-miss events were studied in the study area. Therefore, this study is aimed at assessing the predictors of neonatal near-miss among neonates born at Worabe Comprehensive Specialized Hospital, Southern Ethiopia, 2021 Methods: A hospital-based unmatched case-control study was conducted from November 10, 2021, to November 30, 2021. A pre-tested, structured, and standard abstraction checklist was used to collect the data. After checking the data for completeness and consistency, it was coded and entered into Epi-Data 3.1 and then exported to Stata version 14 for analysis. All independent variables with P-value ≤ 0.25 in bivariable binary logistic regression were entered into multivariable analysis to control the confounding. Variables with p-value < 0.05 were considered statistically significant. Results: In this study, 134 neonatal near-miss cases, and 268 controls were involved. The identified predictors of neonatal near-miss were rural residence [AOR: 2.01; 95% CI: 1.31-5.84], no ANC follow-up visits [AOR: 2.98; 95% CI: 1.77–5.56], antepartum hemorrhage [AOR: 2.12; 95% CI: 1.18–4.07], premature rupture of the membrane [AOR: 2.55; 95% CI: 1.54–5.67], and non-vertex fetal presentation [AOR: 3.05; 95% CI: 1.93–5.42]. Conclusion: The current study identified rural residents, no ANC visits, antepartum hemorrhage, premature rupture of membrane, and non-vertex fetal presentation were found to be significantly associated with neonatal near-miss cases. As a result, local health planners and healthcare practitioners must collaborate in enhancing maternal healthcare services, focusing specifically on the early identification of issues and appropriate treatment. Keywords: neonatal near-miss, predictors, determinant, morbidity, Southern Ethiopia